2024
DOI: 10.1101/2024.03.07.584012
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cognitive modeling of the Mnemonic Similarity Task as a digital biomarker for Alzheimer’s Disease

Casey Vanderlip,
Michael D. Lee,
Craig E.L. Stark

Abstract: AD related pathologies, such as beta-amyloid (Aβ) and phosphorylated tau (pTau), are evident decades before any noticeable decline in memory occurs. Identifying individuals during this asymptomatic phase is crucial for timely intervention. The Mnemonic Similarity Task (MST), a modified recognition memory task, is especially relevant for early AD screening, as it assesses hippocampal integrity, a region affected (both directly and indirectly) early in the progression of the disease. Further, strong inferences o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Indeed, work has found that performance on these tasks is impaired in individuals with Mild Cognitive Impairment (MCI) compared to cognitively normal (CN) older adults 28,29 . Further, these tasks can identify individuals with elevated Aβ and tau prior to cognitive decline 30,31 . However, it is not yet fully known if mnemonic discrimination deficits are predictive of future AD pathology and cognitive decline.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, work has found that performance on these tasks is impaired in individuals with Mild Cognitive Impairment (MCI) compared to cognitively normal (CN) older adults 28,29 . Further, these tasks can identify individuals with elevated Aβ and tau prior to cognitive decline 30,31 . However, it is not yet fully known if mnemonic discrimination deficits are predictive of future AD pathology and cognitive decline.…”
Section: Introductionmentioning
confidence: 99%